Knowledge and practice on green purchasing of personal care products among undergraduate students in Universiti Putra Malaysia - Hana Fateha Hashim,; Haliza Abdul Rahman,; Izzah Nadhirah Mohamed Zain, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Skincare products, hair care, oral care, cosmetics, and products for feminine hygiene are included in the Personal Care Products (PCP). This study was conducted to determine the level of knowledge and practice in the purchase of green personal care products (PCP). A cross-sectional study was done by distributing a modified set of questionnaires containing five sections among undergraduate students at UPM. Respondents (n=276) were obtained through the multistage cluster sampling method. The data were analyzed by using SPSS version 25.0. The results showed that the majority of respondents had high knowledge (48.0%) of green personal care products (PCP). Based on this study, the buying practice of green personal care products was still at a moderate level (73.0%). Chi-square analysis shows that there was a significant relationship between gender with knowledge and practice with p<0.05, (p=0.0001), and (p=0.004) respectively. In addition, there was also a relationship between knowledge and practice (p<0.05). In conclusion, youth are only aware of the importance of choosing green products, but they still continue to buy conventional products, which will negatively affect the environment in the long run. This issue needs to be highlighted to ensure environmental sustainability in the future. Furthermore, the Ministry of Higher Education and Universiti Putra Malaysia needs to strengthen environmental education in university to create more awareness of environmental protection and conservation among undergraduate students.